NIPA (Nuclear Interaction Partner of ALK) Is Crucial for Effective NPM-ALK Mediated Lymphomagenesis - Kreutmair, Stefanie; Lippert, Lena Johanna; Klingeberg, Cathrin; Albers-Leischner, Corinna; Yacob, Salome; Shlyakhto, Valeria; Mueller, Tony; Mueller-Rudorf, Alina; Yu, Chuanjiang; Gorantla, Sivahari Prasad; Miething, Cornelius; Duyster, Justus; et al. (Frontiers in Oncology, 2022)
The NPM-ALK fusion kinase is expressed in 60% of systemic anaplastic large-cell lymphomas (ALCL). Nuclear Interaction Partner of ALK (NIPA) was identified as binding partner of NPM-ALK. To identify the precise role of NIPA for NPM-ALK-driven lymphomagenesis, we investigated various NPM-ALK+ cell lines and mouse models. Nipa deletion in primary mouse embryonic fibroblasts resulted in reduced transformation ability and colony formation upon NPM-ALK expression. Downregulating NIPA in murine NPM-ALK+ Ba/F3 and human ALCL cells decreased their proliferation ability and demonstrated synergistic effects of ALK inhibition and NIPA knockdown. Comprehensive in vivo analyses using short- and long-latency transplantation mouse models with NPM-ALK+ bone marrow (BM) showed an impaired NPM-ALK-induced tumorigenesis with prolonged survival and reduced spleen colonies upon Nipa deletion. To avoid off-target effects, we combined Nipa deletion and NPM-ALK expression exclusively in T-cells using a lineage restricted murine ALCL-like model resembling the human disease: control mice died from neoplastic T-cell infiltration, whereas mice transplanted with Lck-CreTG/wtNipaflox/flox NPM-ALK+ BM showed significantly prolonged survival. Immunophenotypic analyses indicated a characteristic ALCL-like phenotype in all recipients but revealed less "stem-cell-like" features of Nipa deficient lymphomas compared to controls. Our results identify NIPA as crucial player for effective NPM-ALK-driven ALCL-like disease in clinically relevant murine and cell-based models.